Lebenswege erzählen Rekonstruktion biographischer Bewältigungsstrategien von Adoleszenten am Übergang Schule-Beruf - Siegert, Karolina (Perspektiven sonderpädagogischer Forschung, 2021)
The dissertation is located in the context of research on adolescence and transitions with a focus on special education. Disadvantaged adolescents are the target group of this study. Adolescents were interviewed at two points in time using biographical narrative interviews. In addition, parent interviews took place once, which serve as an addition or contrast, but primarily in order to stress the intergenerational contouring of the life phase of adolescence. The focus of the study is on how adolescents experience and handle the transition from school to post-school life. By using biographical case reconstructions, biographical coping strategies and vocational self-presentations were reconstructed from the narratives in order to illuminate the complexity that such transitions pose. The theoretical framework used in this dissertation understands adolescence as embedded in generational relations, which is also viewed in terms of inequality theory. As a result, the perspective on the adolescent life stage is not only focused on adolescent developmental tasks, but is characterized by an intergenerational view that forms the background for complex and dynamic readjustment processes. Thus, persistent familial significance in this phase of life is emphasized. By reconstructing biographical coping strategies, it becomes visible how young people deal with vocational orientation processes against their familial background and what efforts they partly expend to fulfill familial missions or to distance themselves from them. The research design of the study responds to a desideratum that exists with regard to qualitative or biographical long-term studies in the area of adolescence in school and vocational contexts. The life stories of the adolescents clearly point to the necessity of embedding transitions in an overall biographical context and of reacting to the associated ways of looking at the life phase of adolescence. (DIPF/Orig.)